2006
DOI: 10.1016/j.cardiores.2006.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns of electrical remodeling in canine ventricular hypertrophy: Focus on IKs downregulation and blunted β-adrenergic activation

Abstract: Objectives: Electrical remodeling in cardiac hypertrophy often involves the downregulation of K + currents, including β-adrenergic (β-A)-sensitive I Ks . Temporal patterns of ion-channel downregulation are poorly resolved. In dogs with complete atrioventricular block (AVB), we examined (1) the time course of molecular alterations underlying I Ks downregulation from acute to chronic hypertrophy; and (2) concomitant changing responses of repolarization to β-adrenergic receptor (β-AR) stimulation. Methods and Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 35 publications
1
48
0
Order By: Relevance
“…All analysed mechanical parameters were compatible with our earlier work [4,5]. Also, under control conditions, repeated biopsy sampling from the apicolateral LV wall did not significantly influence the expression of cardiomyocyte-specific proteins that have been shown to be altered in remodelling processes early after the induction of AVB [16]. These findings support the minimally invasive character of the technique and are in line with the macroscopic finding of only slight local fibrosis at barely visible puncture sites.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…All analysed mechanical parameters were compatible with our earlier work [4,5]. Also, under control conditions, repeated biopsy sampling from the apicolateral LV wall did not significantly influence the expression of cardiomyocyte-specific proteins that have been shown to be altered in remodelling processes early after the induction of AVB [16]. These findings support the minimally invasive character of the technique and are in line with the macroscopic finding of only slight local fibrosis at barely visible puncture sites.…”
Section: Discussionsupporting
confidence: 86%
“…6). To control for influences of repeated biopsy sampling itself on protein expression, we studied cardiomyocytespecific proteins known to change after AVB, such as the K + -channel sub-unit KCNQ1 and the β-1 adrenergic receptor [16]. The expression level of both proteins remained unaltered in repeated biopsies of three control dogs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, Brooksby et al (5) have shown that the electrical remodeling related to cardiac hypertrophy was restricted to a decrease in I K1 current density with no difference in the resting potential level of cardiomyocytes from control and spontaneously hypertensive rats. The fewer electrophysiological studies available in the literature related to volume-overload induced cardiac hypertrophy showed a decrease in I K (50,56) but an increase in I K1 without any change in I to (56).…”
mentioning
confidence: 88%